CRUD in Designing a Staffing Management Information System for TVRI West Sumatra - Lika Jafnihirda; Giatman -; Hasan Maksum; Firdaus - (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The use of information technology can simplify and accelerate a business process and also the company's performance in managing information. Information processing will be faster if it is accessed on a web page. Therefore, researchers designed a web-based personnel management information system. This system was built using the PHP programming language and MySQL database by analyzing the use of CRUD (Create, Read, Update, Delete ). This is done by inputting employee data more easily. With this staffing management information system, it can make it easier to manage employee data which is easy and fast to be immediately followed up by related parties. This personnel management information system also makes it easier for employees to do work and makes reporting more optimal and timely as needed.